68Ga-DOTATOC PET/CT Imaging of a Muscular Solitary Fibrous Tumor. (1st May 2023) - Richard, Capucine; Cros, Jérôme; Seban, Romain-David; Champion, Laurence; Hescot, Ségolène
Abstract: A 73-year-old woman was referred for 68 Ga-DOTATOC PET/CT staging of a grade 2 pancreatic neuroendocrine tumor, which showed the primary pancreatic tumor, liver metastases, one left pleural metastasis, and high uptake in a mass of the right triceps brachii muscle. Two years before, she underwent 18 F-FDG PET/CT and 111 In-pentetreotide scan, respectively, with low and high uptake of each radiotracer in the triceps mass. Histopathological analysis revealed a solitary fibrous tumor. Immunohistochemistry showed no staining for SSTR-2 and SSTR-5, suggesting tumor overexpression of another somatostatin receptor. This case highlighted a potential pitfall on 68 Ga-DOTATOC PET/CT.